Genetic Diversity and Molecular Phylogeny of Iranian Goats Based on Cytochrome Oxidase I (COXI) Gene Sequences (KERAGAMAN GENETIK DAN FILOGENI MOLEKULER KAMBING-KAMBING IRAN BERDASARKAN SEKUENS GEN CYTOCHROME OXIDASE I (COXI)) - Sharifi, Reza Seyed; Sofla, Sima Savar; Seyedabadi, Hamid Reza (Jurnal Veteriner; Vol 18 No 4 (2017), 2018)
Mitochondrial DNA has been one of the most widely used molecular markers for phylogenetic studies in animals because of its simple genomic structure. This study examines the genetic characteristic of domestic goat using sequence analysis of mitochondrial DNA Cytochrome oxidase subunit I (COXI) to identify and differentiate among three common breeds (Adani, Najdi and Markhoz) of Iran. The genomic DNA was isolated by salting out method and amplified cytochrome oxidase I gene using Polymerase Chain Reaction (PCR) method with a pair of primer. Phylogenetic trees and pairwise calculations were obtained by using Mega 6 software. A partial sequence of cytochrome oxidase I gene of Iranian goats is 1286 bp and contained four variable sites and three haplotypes. Phylogenetic analysis of haplotype in the combination with the goat from GenBank showed that Iranian goatclustered in a separate lineage. This study was found informative for establishing relationships between breeds from different parts of the world. This study may facilitate the future researchers and breeders for better understanding the genetic interactions and breed differentiation for devising future breeding and conservation strategies to preserve the rich animal genetic reservoir of the country.